Effect of Health Literacy Intervention on Medication Adherence among Older Adults with Chronic Diseases - Magda M. Mohsen; Bahiga Galal Abd El-Aal; Sally S. Hassan; Amal A. El-Abbassy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Medication adherence is essential for controlling chronic conditions, treating temporaryconditions, and overall health and well-being. Aim: Examine the effect of health literacy intervention onmedication adherence among older adults with chronic diseases. Design: A quasi-experimental (study andcontrol design). Settings: Family health unit in Dragel village, Menoufia Governorate, Egypt. Sample:a purposive sample of 140 older adults. Tools:1) Interviewing questionnaire that includes; the sociodemographicdata, medical history, medication knowledge, factor affecting medication adherence andphysiological measurement 2) The Medication Adherence Scale. 3) Self-Efficacy for appropriate medicationuse scale. Results: There was remarkable improved medication adherence and self-efficacy in medication usein the study group compared to pre-intervention and the control group. Also, there was improved knowledgeand practice regarding medication use. Also, there was significant control in random blood glucose leveland blood pressure in the study group compared to pre-intervention and the control group. Conclusion: Thehealth literacy intervention was effective in enhancing medication adherence, successful in improving selfefficacyin medication use, and significantly controlling random blood glucose and blood pressure amongolder adults. Recommendation: Health care providers especially nurses should provide regular follow upfor older adults with chronic diseases regarding medication adherence.